PENGARUH MOTIVASI, KOMPENSASI, SERTA BEBAN KERJA TERHADAP LOYALITAS KARYAWAN PADA PT. COSMOPROFT INDOKARYA BANJARNEGARA - Ratna Suryani (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2020)
ABSTRAK Valuable company assets are employees so the company must manage well in order to make an optimal contribution. Then, to be considered by the company is the loyalty of employees because employees who work to feel comfort, full of responsibility, and easily develop all the potential that they have then automatically employees can Maximize its work. This research aims to determine how much impact motivation, compensation, and workload on employee loyalty at Pt. Cosmoproft Indokarya Banjarnegara simultaneously and partially. With a sample number of 100 respondents. The data collection techniques used are observations, interviews and disseminating questionnaires. The data analysis methods used are multiple linear regression analyses as well as hypothesis tests. The results showed that the influence of motivation, compensation, and workload has a significant positive impact on employee loyalty. Keywords: Motivation, Compensation And Workload